Determinan Intensi Berkelanjutan untuk Menggunakan Aplikasi Pembayaran Digital di Indonesia: Peran Mediasi Kepuasan Pelanggan - Wijaya, Robertus Kartono; Keni, Keni (Business Management Journal, 2025)
During the introduction stage of digital payment application, several applications offered discount and cashback in order to increase the technology adoption. However, after the society has adopted it, the discount and cashback have decreased, thereby the promotion became unattractive and could be a barrier for the society’s intention to use the application continuously. Therefore, this research aims to study the factors affecting society’s intention to use digital payment application continuously in Indonesia. This research uses a non-probability sampling by using the convenience sampling technique. Moreover, this research collected the data through questionnaire from 181 respondents. The data was analysed using Partial Least Square – Structural Equation Modelling (PLS-SEM) method. The results showed that perceived usefulness and trust can affect customer satisfaction and continuance intention to use digital payment applications positively and significantly. Confirmation can’t affect the intention significantly, but it can affect customer satisfaction significantly. Customer satisfaction can affect the intention positively and significantly. Meanwhile, customer satisfaction can mediate the influence of confirmation, perceived usefulness, and trust on the intention.